The Challenges of Librarianship in the Expanding Library Service Worldwide - Jordan, Jay (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
Good evening! It is an honor for me to participate in the LIBER conference. LIBER is a very important organization, and OCLC PICA was pleased to become one of the first patron sponsors of LIBER in 2002. We are very interested in strengthening the relationship between our two organizations. OCLC PICA participants are also members of LIBER. Some of you may know that OCLC PICA has paid subscriptions to LIBER for 18 libraries in Eastern Europe since 2000. We are doing so because we want to help these libraries participate in the European library community. This evening I will discuss the challenges of expanding library service worldwide. This is a topic at OCLC that we are very familiar with, because OCLC is a global library cooperative, helping libraries serve people by providing economical access to knowledge through innovation and collaboration. The cooperative is a truly international community. There are some 34,500 libraries in the U.S. that are participating in the OCLC cooperative. There are now approximately 8,000 libraries in 85 countries outside the U.S. that are participating. There are about 3,000 libraries, primarily institutions of higher education, participating in OCLC in Asia Pacific. There are approximately 800 participating institutions in Canada. There are approximately 678 participating institutions in Latin America and the Caribbean. In Europe, the Middle East and Africa, there are approximately 4,100 institutions participating in OCLC. Our cooperative is global indeed. We will be working the coming year to increase not only the numbers on the map, but also the level of participation by libraries and other cultural heritage organizations in our programs and services. What are some the challenges that librarianship faces?